Scoping review of countries' practices missed by health emergency preparedness and response quantitative tools: COVID-19 and Ebola response experiences - Jennifer B Nuzzo; Jessica Bell; John Mbaziira Ssenkusu; Julius Kiwanuka; Mackline Ninsiima (BMJ Publishing Group, 2024)
Introduction After the COVID-19 pandemic and previous disease outbreaks, it is critical to continuously examine the preparedness measurement tools and level of country preparedness for future health emergencies. Existing preparedness quantitative tools, such as the 2021 Global Health Security Index (GHSI) and Joint External Evaluation (JEE) second edition, may not fully reflect the country's actual practices during an outbreak. This scoping review profiles countries' practices, actions and experiences during Ebola and COVID-19 pandemics missed by these tools but critical to a successful response.Methods Using the PRISMA checklist for scoping reviews, we documented country practices during health emergence responses. Our search strategy keywords included "actions/practices," "preparedness/response," "Ebola/COVID-19," and "successes/experiences/challenges," across PubMed, Medline, CINAHL, Embase, Google Scholar and WHO IRIS. English peer-reviewed articles published between January 2004 and October 2020 for Ebola and between January 2020 and December 2022 for COVID-19 were included. Articles were independently assessed for inclusion and discordant decisions were agreed on by consensus. A qualitative thematic analysis was conducted and findings were presented by a disease outbreak.Results Out of 1913 studies screened, 36 were included. The COVID-19 and Ebola response practices, actions, and experiences not included in the GHSI 2021 and JEE second edition tools included; use of previous outbreaks lessons, cushioning the populations and putting in place mechanisms to support businesses, protection of vulnerable populations, leveraging the trust in leadership and role models, and innovative ways of engaging the public through use of technology.Conclusion Countries' outbreak response strategies depend on the available resources, the outbreak characteristics, its effects and how other countries are responding. This study suggests incorporating capacities of these response actions into existing tools and countries should make detailed plans on how they can leverage existing trust, protect the vulnerable, cushion citizens and businesses from epidemic effects, and innovatively use technology to engage the public in epidemic responses.